Aberrant functional connectome gradient and its neurotransmitter basis in Parkinson's disease - Tao Guo; Cheng Zhou; Jiaqi Wen; Jingjing Wu; Yaping Yan; Jianmei Qin; Min Xuan; Haoting Wu; Chenqing Wu; Jingwen Chen; Sijia Tan; Xiaojie Duanmu; et al. (Neurobiology of Disease, 2025)
Patients with Parkinson's disease (PD) exhibit heterogenous clinical deficits not only in motor function, other deficits in both sensory and higher-order cognitive processing are also involved. Connectome studies have suggested a primary-to-transmodal gradient and a primary-to-primary gradient in functional brain networks, supporting the spectrum from sensation to cognition. However, whether these gradients are altered in PD patients and how these alterations associate with neurotransmitter profiles remain unknown. By constructing functional network and calculating its gradient in 134 PD patients and 172 normal controls, we compared functional connectivity gradients between groups and performed spearman correlation to explore the association between neurotransmitter expression and functional network gradient-based alternations in PD. Decreased first gradients were detected mainly in association cortex, including frontal cortex, insula, cingulate, and parietal cortex, corresponding to the decrement of frontoparietal/ventral attention network observed in network-level analyses. Decreased second gradients were observed in primary motor and somatosensory cortex, meeting the decrement of somatomotor network at the network level. Besides, network-level comparisons revealed the increment of visual network in the first gradient and increment of ventral attention network in the second gradient. Transcription-neuroimaging association analyses showed that changes of the first gradient were mainly negatively correlated with nondopaminergic system, while alterations of the second gradient were positively correlated with both dopaminergic and nondopaminergic systems. These results highlight the connectome gradient dysfunction in PD and its linkage with neurotransmitter expression profiles, providing insight into the molecular mechanisms for functional alterations underlying PD.